NEUROHUMORAL CHANGES IN CHRONIC HEART FAILURE - Spinarova, Lenka; Vitovec, Jiri (Biomedical papers, 2007)
Background: Humoral systems play an important role in the patophysiology and development of chronic heart failure (CHF).Methods: We conducted a search of neurohumoral activation in heart failure and its risk in the development of CHF. Results and conclusion: Neurohumoral factors may be divided into vasoconstrictive, vasodilative and cytokines. The main vasoconstrictive systems are the renin-angiotensin-aldosterone system (RAAS) and the sympathoadrenal system (SAS). Cytokines include tumour necrosis factor (TNF) alpha and interleukins. The systems of actions are interconnected and they mutually influence their secretion and activities. The possibilities of their detection and assessment for clinical purposes depend on their changes and kinetics in the organism and on the activity of individual metabolites. Apart from their vasoactive effects, the majority of humoral actions also interfere in the process of remodelling, function of the endothelium, blood elements, cardiomyocytes, cells of the smooth muscles, and in immunity as well as inflammatory processes. The rapid development of knowledge on the humoral actions in recent years has made possible their utilisation in diagnostics, treatment and prognosis.
Keywords: Heart failure/Humoral activation/Cytokines